(untitled) (Medico Legal Update, 2019)
Background/Objectives: This study was conducted in order to determine the validity of developing a license system for qualified dying well education training experts by identifying the need of the dying well education and license system. Method/Statistical Analysis: A survey was conducted from April 20 to May 20, 2018 for 54 professional lecturers who completed the education course for training dying well instructors, and the statistical program R was used for the analysis. All items in the questionnaire except the general characteristics of subjects were composed of 4-point Likert scale(“Very unnecessary” was 1point, “unnecessary” was 2 points, “necessary” was 3 points, and “Very necessary” was 4 points.). Findings: According to the result of measuring the need for dying well education expert license education contents, the average score for each subject was found to be as follows: Thanatology 3.40 points( ± 0.63), care for terminally ill patients (hospice) 3.56 points( ± 0.56), communication 3.38 points( ± 0.59). Improvements/Applications: In the future, it is necessary to provide systematic and integrated death education through the training of qualified education experts and the composition of subjects according to the necessities of the curriculum of the professional dying well education.